2017
DOI: 10.1007/s41252-017-0035-3
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use in Individuals with Mild to Borderline Intellectual Disability: an Exploration of Rates and Risks in the Netherlands

Abstract: Little is known about rates and risk factors of substance use (SU) in individuals with mild to borderline intellectual disabilities (MBID,. This hinders targeted prevention and treatment. In this study we assessed SU rates and risk factors in individuals with MBID in 419 adults (63% male, average IQ = 66) in 16 Dutch disability services. Lifetime and current SU, SU picture recognition, knowledge, attitudes and modeling were assessed with the Substance use and misuse in Intellectual Disability -Questionnaire (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…To measure lifetime and current alcohol and drugs use, we used the Substance Use and Misuse in Intellectual Disability -Questionnaire (SumID-Q; VanDerNagel, Kiewik, Van Dijk, De Jong, & Didden, 2011;Van Duijvenbode, Didden, Korzilius, Trentelman & Engels, 2013). Substances (i.e., alcohol, cannabis, ecstasy, heroin, cocaine, speed and magic mushrooms) are introduced with images and only if the participant is familiar with a substance further questions about its use are asked.…”
Section: Substance Usementioning
confidence: 99%
See 2 more Smart Citations
“…To measure lifetime and current alcohol and drugs use, we used the Substance Use and Misuse in Intellectual Disability -Questionnaire (SumID-Q; VanDerNagel, Kiewik, Van Dijk, De Jong, & Didden, 2011;Van Duijvenbode, Didden, Korzilius, Trentelman & Engels, 2013). Substances (i.e., alcohol, cannabis, ecstasy, heroin, cocaine, speed and magic mushrooms) are introduced with images and only if the participant is familiar with a substance further questions about its use are asked.…”
Section: Substance Usementioning
confidence: 99%
“…Lifetime use was assessed with the item 'Have you ever used alcohol/cannabis/hard drugs?' Response options were: (1) 'no' and (2) 'yes' (VanDerNagel, Kiewik, Van Dijk et al, 2011;Van Duijvenbode et al, 2013). Current substance use was assessed with the item: 'Did you use alcohol/cannabis/hard drugs in the last month?'…”
Section: Substance Usementioning
confidence: 99%
See 1 more Smart Citation
“…Although high rates of substance use have been reported in some studies (van Duijvenbode et al, 2015), the prevalence of substance-related disorders among individuals identified to have ID is estimated to be between 0.5-6% (Cooper et al, 2007;Lin et al, 2016;Slater, 2010a;Sturmey, Reyer, Lee, & Robek, 2003). Studies on substance use typically report that tobacco and alcohol are the most commonly used legal substances and that cannabis is the most commonly used illicit drug (VanDerNagel et al, 2017;vanDuijvenbode et al, 2015).…”
Section: Prevalencementioning
confidence: 99%
“…There has been a growing recognition that individuals with intellectual disability (ID) may have a comorbid substance use disorder (SUD). During the last ten years, there has been an increase in the body of literature on adapted assessment and treatment of SUD among individuals with ID and borderline intellectual functioning and the understanding and recognition of the special needs of individuals with these dual conditions has improved (Didden, 2017;Kerr, Lawrence, Darbyshire, Middelton, & Fitzsimmons, 2013;VanDerNagel, Kemna, & Didden, 2013;VanDerNagel et al, 2017;van Duijvenbode et al, 2015).…”
Section: Introductionmentioning
confidence: 99%